Experimental and theoretical investigations of electronic structure and optical in Ln3+-doped In2S3 nanoparticles. (15th September 2022) - Li, Zhifang; He, Bintai; Yu, Suye; Qiao, Yuancun
Abstract: Indium sulfide (In2 S3 ) quantum dots have emerged as one of the most promising chalcogenide semiconductor nanoparticles for high transparency in the visible region with excellent photoelectric performance and environmental friendliness. Moreover, lanthanide ions have excellent optical properties and rich energy level structure, which has aroused widespread concern. Cubic-phase pure In2 S3 and Ln 3+ -doped In2 S3 (Ln = Dy, Ho, Tb) nanoparticles were prepared using an efficient gas–liquid phase chemical method, and the growth mechanism was proposed and discussed. The absorption spectrum shows the quantization size effect and the change in the band gap value due to the introduction of lanthanide ions. The band gap value decreases upon Dy 3+ doping and increases in Ho 3+ - and Tb 3+ -doped In2 S3 nanoparticles compared with pure In2 S3 . Results were validated and confirmed by computer simulation. Moreover, impurity formation energy was calculated to be negative, indicating that the process of incorporating impurity into the host to replace host atoms is relatively unproblematic in experiments. Thus, this study has important guiding significance for the theoretical design and experimental synthesis of unique Ln 3+ -doped semiconductor nanomaterials. Highlights: In2 S3 and In2 S3 :Ln 3+ nanoparticles have been prepared using gas–liquid phase chemical method. Ln 3+ doped In2 S3 nanoparticles have single crystal properties. The band gap energy values are closely related to doping lanthanide ions. The impurity formation energy of In2 S3 :Ln 3+ systems are calculated to be negative.